THE INFLUENCE OF BRAND AWARENESS, PRICE FAIRNESS, AND PRODUCT INNOVATION ON PURCHASE DECISION IN CONSUMERS AI-CHA OUTLET - Ni Luh Gede Anjeli Sasmitha Feby; Putu Yudi Setiawan, Ni Made Rastini, I Made Dana (Adisam Publisher, 2024)
The food and beverage industry is one industry that continues to experience growth. Since 2020, penetration of food and beverage products from China has begun to grow rapidly in the Indonesian market, marked by the establishment of many ice cream and tea processing franchises, one of which is Ai-CHA. This research aims to determine the influence of brand awareness, price fairness, and product innovation on purchase decisions among consumers of Ai-CHA outlets in Denpasar City. This research used a purposive sampling technique with a total of 150 respondents. The analysis tool used is IBM SPSS Statistics. The results of the analysis from this research are: 1) brand awareness has a positive and significant effect on purchase decisions; 2) price fairness has a positive and significant effect on purchase decisions; 3) product innovation has a positive and significant effect on purchase decisions. The implication of this research is that Ai-CHA management pays more attention to brand awareness, price fairness and product innovation in products in the hope of influencing consumer purchasing decisions. Through aspects of brand awareness, price fairness and product innovation that are good for consumers, Ai-CHA is able to create purchase decisions.